Input-output-outcome innovation model: an analysis of the Brazilian manufacturing companies - Fabiane Letícia Lizarelli; Artur Yuiti Ishizaka; José Carlos de Toledo (Innovation & Management Review, 2024)
Purpose - The objectives of this study are to identify which inputs are most relevant for development and successful introduction of product and process innovations and identify the impacts of these two types of innovation on the performance of Brazilian manufacturing companies. Design/methodology/approach - This study analyzes the relationships between input, output and outcome for a sample of 5,586 Brazilian manufacturing companies by using partial least squares structural equation modeling (PLS-SEM). Findings - The results indicate that (1) product innovations are favored by internal resources, (2) process innovations are favored by external resources, (3) product innovations mainly affect a range of products offered by companies and (4) process innovations mainly affect performance in manufacturing capacity, flexibility and costs. Practical implications - By identifying the main efforts to improve the innovation performance and input-output-outcome relationships, the results can contribute to a better decision-making process for innovation investments and management in companies as well as for policymakers. The results are particularly relevant given that the Brazilian case can serve as a reference for other emerging countries. Originality/value - Analyses of the innovation in input-output-outcome relationships were performed in a comprehensive way by using a set of variables for defining each construct. This allowed each construct to be better measured, which improved the understanding of the relationships between inputs and outcomes mediated by product and process innovations.
Keywords: 650; Innovation inputs; Innovation outputs; Innovation outcomes; PLS-SEM; Manufacturing sector; Innovation policy; Innovation management